“That Kids Are Reading Is More Important than What Kids Reading:” - Leilya Pitre (Study and Scrutiny, 2025)
This interview with Jeffrey Kaplan, past president of ALAN (2012-2013), delves into his professional journey, experiences with ALAN, and his unwavering dedication to promoting Young Adult (YA) literature. Dr. Kaplan shares his path from teaching high school to working alongside influential figures like Ted Hipple, Gary Salvner, Jerry Weiss, Don Gallo, and many others, highlighting ALAN's evolution from a grassroots initiative to a nationally recognized organization. He discusses the significance of The ALAN Review as a peer-reviewed journal, its achievements, and areas for growth, particularly in fostering research and public awareness of YA literature. Throughout, Kaplan emphasizes ALAN's core belief: it is more important that kids are reading than what kids are reading, underscoring the crucial role of YA literature in inspiring young people and addressing contemporary social issues.